Make immunological peace not war: Potential applications of tolerogenic dendritic cells - Walton, Emma Louise (Biomed J, 2017)
In this issue of the Biomedical Journal, we explore the powerful immunosuppressive properties of tolerogenic dendritic cells and discuss their potential to bring about lifelong tolerance in transplantation and autoimmune disease. We also highlight an exciting new development in the field of malaria diagnosis that could facilitate early detection of the disease.